Antioxidant compounds and activity from the leaf of the mistletoe (Dendrophthoe pentandra (L.) Miq.) on Duku plant (Lansium domesticum Corr.) - Salni; Hanifa Marisa; Putri Mayasari (Universitas Ahmad Dahlan, 2023)
Mistletoe, known in Indonesia as benalu, is a parasitic plant that can thrive on a variety of hosts. This study determined that Dendrophthoe pentaphylla (L.) Miq. was accountable for the antioxidant activity of mistletoes growing on Duku (Lansium domesticum Corr.). This study aims to assess the antioxidant potency in the fractions of n-hexane, ethyl acetate, and methanol-water, as well as to identify the chemical groups and IC50 values. Extraction by maceration, fractionation by liquid fractionation method, isolation by vacuum liquid chromatography (VLC) and column chromatography, and DPPH assay for antioxidant activity were employed in this study. The n-hexane and ethyl acetate fractions exhibited antioxidant activity, but the methanol fraction showed minuscule activity. NH.1 (compounds from the N-hexane fraction followed by VLC were found in eluate 1) and NH.3 (compounds from the N-hexane fraction followed by VLC were found in eluate 3) were successfully isolated from the n-hexane fraction. The former was identified as terpenoids, while the latter belonged to flavonoids. The ethyl acetate fraction yielded the flavonoid EA.3 (compounds from the ethyl acetate fraction followed by VLC were found in eluate 3), which was isolated from the ethyl acetate fraction. Compound NH.1 showed weak antioxidant activity indicated by IC50 value of 151.35 g/mL. Meanwhile, NH.3 and EA.3 were categorized as moderate, proven by IC50 values consecutively of 96.64 and 78.37 g/mL.